MCITP : - Johnson, Eric (Wiley Pub., 2007)
If you set up, maintain, and troubleshoot desktop applications on Windows Vista, now you can build your skills and take the next step towards your MCITP: Enterprise Support Technician, Microsoft's new job-based certification track for desktop support professionals. With this in-depth guide, you'll learn how to support Vista in an enterprise setting, plus have the perfect study tool to help you prepare for exam 70-622. Find full coverage of all exam objectives, practical hands-on exercises, challenging review questions, a CD with testing software and electronic flashcards, and more.